2012
DOI: 10.1158/0008-5472.can-12-0334
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Glioblastomas to Clinically Available MEK Inhibitors Is Defined by Neurofibromin 1 Deficiency

Abstract: Loss of neurofibromin 1 (NF1) leads to hyperactivation of RAS, which in turn signals through the RAF/MEK/ ERK and phosphoinositide 3-kinase (PI3K)/mTOR pathways to regulate cell growth and survival. Because NF1-deficient acute myeloid leukemias are sensitive to MEK inhibitors, we investigated here whether NF1-deficient glioblastoma multiforme (GBM) would respond to MEK inhibition. In 19 GBM cell lines, we found that treatment with the clinically available MEK inhibitors PD0325901 or AZD6244 decreased levels of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 37 publications
2
82
0
Order By: Relevance
“…Previous work has shown that NF1 -deficient GBM cells have variable degrees of MEK inhibitor sensitivity (See et al, 2012). This relative MEK inhibitor sensitivity was also observed in o-GSCs, which results from MEK/CRAF binding and CRAF activation such that treatment with a MEK inhibitor (trametinib) that additionally promotes the dissociation of MEK from CRAF effectively blocked o-GSC growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that NF1 -deficient GBM cells have variable degrees of MEK inhibitor sensitivity (See et al, 2012). This relative MEK inhibitor sensitivity was also observed in o-GSCs, which results from MEK/CRAF binding and CRAF activation such that treatment with a MEK inhibitor (trametinib) that additionally promotes the dissociation of MEK from CRAF effectively blocked o-GSC growth.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacodynamic analyses of intratumoral MAPK, PI3K and mTOR signaling were not completed leaving the cause of the lack of efficacy unresolved (46-48). Other agents, possibly those directly inhibiting Raf[mgn]MEK[mgn]Erk signal cascades, such as the MEK inhibitor AZD6244, may also curtail ON123300-induced Erk activation (49, 50); however with the gefitinib-ON123300 combination not only was Erk activation suppressed Akt inhibition was enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that other tumors driven by NF1 loss, including PA associated with neurofibromatosis, may be amenable to small molecule inhibition of downstream targets in the MAPK pathway (8). …”
Section: Introductionmentioning
confidence: 99%